FINE STRUCTURE OF SHORT-PERIOD SEISMIC FIELDS AS MEASURED WITH A SEISMIC ARRAY - Kaazik P.B.; Kopnichev Yu.F.; Nersesov I.L.; Rakhmatullin M.Kh. (My University, 1989)
In the present paper, we shall investigate the spatial and temporal characteristics of short-period seismic fields by analyzing high-quality data obtained with a small seismic array that our Institute has operated for a month in southern Kazakhstan near the Ili River. The most important result of our investigations concerns the spatial and temporal structure of the Lg wave coda. We therefore conclude that the Lg coda consists of a set of transverse waves that have been singly or multiply reflected from weak crustal and mantle reflectors. A curious result that follows from our investigation is that a crustal phase consisting of transverse waves with kinematic characteristics similar to those of the Lg group is emitted in most earthquakes that occur at great depths in the Hindu Kush. It is readily seen that such a wave group could not form in a purely horizontally stratified model of the crust. The only possible explanation of its occurrence, we believe, is scattering of S waves by surface relief and the M discontinuity that results in their effective capture by the crustal waveguide. The data that we have presented provide a reliable empirical basis for recent methods of determining absorption in the upper mantle from the Lg or Sn coda.